Menelusuri Tren Riset Terkait Teknologi Pendidikan dalam Pendidikan Inklusif: Sebuah Tinjauan Bibliometrik - Izzul Kiram Suardi; Jumriani Sultan; Sofi Septiani Julaeha Nursaniah; Zafrullah Zafrullah; Muhammad Afiq Ikhmal Bin Suhaimi; Rahayu Nurfadilla (Perspektif Pendidikan dan Keguruan, 2025)
This research aims to map trends, collaboration, and future research focuses in the field of inclusive education technology. Using a bibliometric approach based on the PRISMA framework, articles published in Scopus (2007–2024) were identified, filtered, and analyzed. Bibliographic and citation data are extracted and then processed with RStudio for publication trend analysis, VOSviewer to visualize collaboration networks and topic clusters, and PoP to calculate citation metrics. The results of the study revealed a substantial increase in the number of publications since 2007, with a peak in productivity in 2021. Five main clusters were identified: assistive technology, intellectual disability, UDL, AR, and global collaboration. Network analysis shows that international collaboration strengthened during the COVID-19 pandemic, signaling the crucial role of online platforms and digital tools in maintaining the sustainability of inclusive learning. The implications of this research include recommendations for developing a technology-integrated UDL framework, post-pandemic innovations in the form of AI-based adaptive learning systems, and expanding cross-disciplinary collaboration to study various fundamental topics in more depth. The study's limitations lie in the single use of the Scopus database; follow-up studies are recommended to involve other sources such as the WoS and ERIC to gain more diverse and comprehensive insights.